2013
DOI: 10.1179/1743281212y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Oxidising roasting behaviours of anthracite containing haematite pellets

Abstract: In this investigation, the roasting features of haematite pellets to which a small amount of anthracite was added and the effects of carbon on the induration behaviours of the pellets were studied. The results indicate that the suitable dosage of pulverised anthracite is 1?0-1?5%. During the roasting, part of the original haematite grains in the pellets are reduced to magnetite, and some original haematite grains are decomposed into magnetite. Then, the newborn magnetite is oxidised to secondary haematite, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Generally, a liquid window is the optimal Ca addition amount for Ca‐treated steel to avoid the formation of solid inclusions. [ 29,30 ] As shown in Figure 10, the T.Ca content range for the liquid windows was 8–14 ppm, which was too narrow and hard to control. Solid CaS inclusions began to form in molten steel when the T.Ca content increased to 14 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a liquid window is the optimal Ca addition amount for Ca‐treated steel to avoid the formation of solid inclusions. [ 29,30 ] As shown in Figure 10, the T.Ca content range for the liquid windows was 8–14 ppm, which was too narrow and hard to control. Solid CaS inclusions began to form in molten steel when the T.Ca content increased to 14 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FactSage is often used to calculate the liquid windows of Ca treatment for modified inclusions, enabling precise control of calcium addition. [ 27–30 ] Several studies [ 28,30 ] have shown that T.S narrows the liquid windows, while T.O and higher temperature widen the windows.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of Mag unoxidized in the heat-treated pellet is an indicative of the low efficiency of the sintering process since all this iron oxides phases should be present in the +3 oxidation state because of the oxidizing environment of the induration process. Previous works ofJiang et al (2008),Li et al (2012) andTang et al (2013) described this type of behavior where the reduction rate of Hem to Mag is faster than the oxidation of the newborn Mag into secondary…”
mentioning
confidence: 95%